Pseudoagoraphobia, a Diagnostic Clue in Stiff‐Limb Syndrome. Issue 3 (5th March 2020) - Marano, Massimo; Motolese, Francesco; Lanzone, Jacopo; Di Santo, Alessandro; Rossi, Mariagrazia; Bevacqua, Maria Gabriela; Ranieri, Federico; Capone, Fioravante; Gatto, Emilia Mabel; Di Lazzaro, Vincenzo
ABSTRACT: Background: Stiff‐limb syndrome is part of stiff person spectrum, presenting with fluctuating gait disorders attributed to leg stiffness, spasms, and posturing. It could also manifest with anxiety and specific phobias such as pseudoagoraphobia. We aimed to describe the importance of specific gait phobia as a diagnostic clue to anti–glutamic acid decarboxylase stiff‐limb syndrome. Cases: We reported on 2 cases of stiff‐limb syndrome sharing a similar diagnostic path and phenomenology. Both were featured by pseudoagoraphobia, which has documented to typically cover organic conditions, and a remarkable diagnostic delay attributed to misdiagnoses. Presence of pseudoagoraphobia should not point to the diagnosis of a functional disorder—although a negative instrumental workup is documented. Conclusions: Both cases are emblematic of the high misdiagnosis rate affecting stiff person syndrome patients. A proper diagnostic process, including the identification of a pseudoagoraphobia, should help in reaching a diagnosis and providing an early and effective treatment. Abstract : View Supplementary Video